Habilidades sociais e grau de dependência em pacientes tabagistas internados pela cirurgia vascular em hospital terciário - Cury, Laura Lemos (2018)
Tobacco is one of the leading causes of premature death in the world and its dependence is maintained by nicotine and determined by biological, behavioral, psychological and sociocultural processes. Intensified consumption makes abstinence symptoms more probable to appear. The social factors that contributed to the experimentation become less motivating and the dependence happens to be controlled by the avoidance of the symptoms of the abstinence. The continued use of the cigarette causes changes in brain physiology that makes its cessation process something continuous and complex. Some triggers identified as abstinence-hindering refer to deficits in social skills. The term HS is used to designate learned behavioral capacities that involves social interactions. The present study was conducted from February to March 2017 and evaluated and correlated degree of nicotine dependence and social skills in sixty smokers patients hospitalized by vascular surgery team at a general hospital in the interior of the State of São Paulo, with the purpose of suggesting a therapeutic group where the deficits in social skills found in this study will be able to be work on. A descriptive type of search was performed. Participants were approached and invited to participate in the research whose data were analyzed quantitatively. Of the 60 participants, 23 were women and 37 were men, mean age was 62.85 years, with 52.51 years using cigarette. Only 18.33% tried to stop smoking and the beginning of use for them were at 10.33 years. Only 21.66% of the dependents did not have a smoker's family member, and 5% reported that their support group were non-smoker. According to the Fagerström test for nicotine, the majority of the evaluated patients have low and medium degree of dependence (adding up the two values). For social skills, the total scores for both genders correlate with the Fagerström test, which shows that the more dependent the more socially skilled, which may mean that the tobacco user feels socially skillful without being, if it is so, largely from a social skills training as part of the smoking cessation treatment.